YOUTH. The Future of Reindeer Herding Peoples. Arctic Council EALLIN Reindeer Herding Youth Project 2012-2015. - International Centre for Reindeer Husbandry (ICR); Association of World Reindeer Herders (WRH); UArctic EALÁT Institute (UEI) (Sustainable Development Working Group (SDWG), 2015)
Draft report from the Sustainable Development Working Group for the project 'EALLIN - The Voice of the Reindeer Herding Youth 2012-2014'. Submitted to the Arctic Council's Senior Arctic Officials meeting in Whitehorse, Canada, March 4-5. NOTE: This version of the report has not been approved by Ministers. For the final approved version of the report, please see the documents from the Arctic Council's Ministerial meeting in Iqaluit 2015, or follow this link: https://oaarchive.arctic-council.org/handle/11374/408.